The relationship of hyperlipidemia with maternal and neonatal outcomes in pregnancy: A cross-sectional study - Seyedeh Hajar Sharami; Zahra Abbasi Ranjbar; Fatemeh Alizadeh; Ehsan Kazemnejad (Shahid Sadoughi University of Medical Sciences, 2019)
Background Concentrations of plasma lipids levels during pregnancy clearly increases. According to some studies, dyslipidemia is effective in the incidence of preeclampsia and insulin resistance. Objective: This study aimed to examine the relationship between hyperlipidemia and maternal and neonatal outcomes in pregnant women. Materials and Methods This is a cross-sectional study which was conducted on two groups of pregnant women with hyperlipidemia and normal ones to assess maternal and neonatal outcomes. Maternal data including gestational age, mother's age, body mass index, and maternal weight gain during pregnancy, gestational diabetes mellitus, preeclampsia, cholestasis, and delivery method. Also, birth weight and Apgar score were gathered as the neonatal outcomes. Results The results showed that the prevalence of abnormal lipid parameters increased with increasing gestational age. In pregnant women with dyslipidemia in combination with increased triglyceride, cholesterol and Low-density lipoprotein, and decreased High-density lipoprotein, the incidence rates of gestational diabetes (p < 0.001), preeclampsia (p < 0.001), cholestasis (p = 0.041), fetal growth retardation (p < 0.001), and macrosomia (p < 0.001) were statistically higher. Conclusion Dyslipidemia was associated with some adverse effects of pregnancy and harmful fetal outcomes. Therefore, it seems that adding laboratory assessment of lipid profiles before and during pregnancy can be effective in early diagnosis of dyslipidemia.